MiR-7 Regulates Pathogen-Induced Immune Response via PAK1 in the Sea Cucumber Apostichopus japonicus - Zhao, Tanjun; Ren, Liyuan; Li, Chengda; Liu, Li; Zou, Yang; Yan, Hanyu; Zhan, Yaoyao; Chang, Yaqing (Frontiers in Immunology, 2022)
MicroRNA-7 (miR-7) is a highly conserved short non-coding RNA involved in various bioprocesses via the regulation of multiple target genes. To enrich our knowledge of the functions of miR-7 in innate immune regulation in echinoderms, we first investigated the targeting relationship between miR-7 and PAK1 in the sea cucumber Apostichopus japonicus and then explored the functions of miR-7, the PAK1 gene, and the miR-7/PAK1 axis in the pathogen-induced immune response of A. japonicus. Our results showed that miR-7 can bind to the 3ʹUTR of PAK1 and negatively regulate the expression of PAK1 in A. japonicus. Overexpression and inhibition of miR-7 and inhibition of the expression of PAK1 can alter phagocytosis, cellular agglutination, and lysozyme contents in A. japonicus. Both miR-7 and the PAK1 gene are involved in immune defense against Vibrio splendidus infection; the miR-7/AjPAK1 axis showed immune regulatory function at 48 to 72 h post-infection (hpi) after V. splendidus infection in A. japonicus. In summary, the results of this study established that miR-7 regulates the pathogen-induced immune response by targeting PAK1 in A. japonicus.